Media Coverage of Police Sexual Misconduct in Seven Cities: A Research Note - Lopez, Kristina M. (American journal of criminal justice, 2017)
As a supplemental component of a larger confidential analysis of police sexual misconduct (PSM) in “Central City”, this study examines news accounts of PSM events in seven comparable metropolitan cities in the United States. Google search was used to identify media news reports to estimate PSM, standardized for city population and size of police force. Findings indicate that PSM rates vary by city, events typically implicate a male officer and a female victim, and most media reports involved an arrest that may signal under-reporting. Observation of commonalities across the sample cities informs discussion of the need for transparency and preventative measures.